Mitigation strategies to manage rapport in the interaction between the Iraqi veterinary students and their clients - Ahmed, Wasan Khalid; Alkhawaja, Hussein Walid; Nimehchisalem, Vahid; Krishan, Tamara (Indonesian Journal of Applied Linguistics, 2024)
Soliciting accurate information about animals’ medical cases and maintaining harmonious relationships with clients require vets to use several mitigation strategies. This study analysed hedges, bushes and shields proposed as mitigation strategies by Caffi (2007). In light of the Rapport Management Theory conceptualized by Spencer-Oatey (2008), the analysis was extended to include defining the roles of these strategies in expressing the relational work in terms of the interactional goals, sociality rights and obligations, and face sensitivities. For this purpose, the data were collected using a mixed-mode approach through audio-recordings and a client-satisfaction questionnaire, and then analysed using a discourse analysis (DA) following Dörnyei (2007). The findings showed that the Iraqi veterinary students employed bushes, hedges, and shields to mitigate their speech with the bushes were the most frequently used. The use of these mitigators enabled the veterinary students to shield themselves against any future risks, solicit accurate information about the medical case of the animal, express politeness, maintain solidarity and build good rapport with the clients. For clients, using these devices by the veterinary students enhanced clients’ face sensitivities, equity rights and identity, so they felt appreciated and valued. The findings about clients’ satisfaction revealed that Iraqi veterinary students need to increase their clients’ satisfaction by sharing the medical decision with clients and engaging clients regarding their animals during the medical visit. The findings would inform better veterinary students’ practices at the personal and interpersonal levels. The findings had also some pedagogical implications for veterinary stakeholders to improve veterinary students’ knowledge of the mitigation strategies through giving training courses that aims at improving the delivery of the communication skills within veterinary practice.